Low‐complexity near‐optimal detection of dc2‐balanced codes. Issue 9 (1st April 2016) - Immink, K.A.S.
Abstract : Two constructions of a low‐complexity near‐optimal detection method of dc 2 ‐balanced codes are presented. The methods presented are improvements on Slepian's algorithm for optimal detection of permutation codes.